Stigma toward mental and physical illness: attitudes of healthcare professionals, healthcare students and the general public in Pakistan. Issue 5 (September 2020) - Husain, Muhammad Omair; Zehra, Syeda S.; Umer, Madeha; Kiran, Tayyaba; Husain, Mina; Soomro, Mustafa; Dunne, Ross; Sultan, Sarwat; Chaudhry, Imran B.; Naeem, Farooq; Chaudhry, Nasim; Husain, Nusrat
Abstract : Background: The evidence base for stigma in mental health largely originates from high-income countries. Aims: This study from Pakistan aimed to address the gap in literature on stigma from low- and middle-income countries. Method: This cross-sectional study surveyed 1470 adults from Karachi, Pakistan. Participants from three groups (healthcare professionals, healthcare students and the general public) completed the adapted Bogardus Social Distance Scale (SDS) as a measure of stigma. Results: All three groups reported higher scores of stigma toward mental disorders compared with physical disorders. SDS scores for mental illness in the general public were significantly higher than in healthcare students (mean difference (MD) 6.93, 95% CI 5.45–8.45, P < 0.001) and healthcare professionals (MD 6.93, 95% CI 5.48–8.38, P < 0.001). However, SDS scores between healthcare students and healthcare professionals were not significantly different (MD 0.003, 95% CI −1.14–1.14, P > 0.99). Being female was associated with lower stigma scores and being over the age of 30 years was associated with higher stigma scores. Conclusions: Stigma campaigns in Pakistan need to target the general population. However, evidence of negative attitudes toward mental illness in healthcare students and healthcare professionals supports the need for stronger emphasis on psychiatric education within undergraduate and postgraduate training in Pakistan.